Sedative use and incidence of falls and hip fractures among older adults in an outpatient geriatric clinic - Nelson Machado do Carmo Júnior; Edna Afonso Reis; Antônio Ignácio de Loyola Filho; Estevão Alves Valle; Daniela Castelo Azevedo; Mariana Martins Gonzaga do Nascimento (Geriatrics, Gerontology and Aging, 2023)
Objective: To investigate the use of sedatives by older adults attending a private outpatient geriatric clinic in Belo Horizonte (MG), Brazil, and its association with falls and hip fractures. Methods: Using a longitudinal design, the prevalence of benzodiazepine and nonbenzodiazepine (“z-drugs”) intake by older adults was described and their association with the incidence of falls and fractures (30 days after the initial visit) was evaluated through logistic regression. Results: A total of 7821 older adults were included in the study, most of them women (72.50%), with a mean age of 77.5 years and a mean Clinical-Functional Vulnerability Index (IVCF-20) score of 16.5. The overall prevalence of sedative use (any sedative) was 6.19%, with 4.48% benzodiazepines and 1.98% z-drugs. The most widely used sedatives were clonazepam (29.04%), zolpidem (28.65%), and alprazolam (23.44%). Falls were reported for 182 patients (2.33%), with a higher incidence among users of any sedatives (4.34; p = 0.002; OR = 1.94, adjusted for sex, age, and IVCF-20) and benzodiazepines (5.14%; p < 0.001; OR = 2.28) than among non-users (2.19%). Hip fractures occurred in 33 patients (0.42%), and again were more frequent among users of sedatives (1.03%; p = 0.032; OR = 2.57) and benzodiazepines (1.43%; p = 0.003; OR = 3.45) than among non-users (0.38%). Conclusions: The use of sedatives, especially benzodiazepines, is associated with an increased incidence of falls and hip fractures in older adults.